2020
DOI: 10.1007/s10620-020-06110-y
|View full text |Cite
|
Sign up to set email alerts
|

HIV, Sexual Orientation, and Gut Microbiome Interactions

Abstract: Recent studies have raised interest in the possibility that dysbiosis of the gut microbiome (i.e., the communities of bacteria residing in the intestine) in HIV-infected patients could contribute to chronic immune activation, and, thus, to elevated mortality and increased risk of inflammation-related clinical diseases (e.g., stroke, cardiovascular disease, cancer, long-bone fractures, and renal dysfunction) found even in those on effective antiretroviral therapy. Yet, to date, a consistent pattern of HIV-assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 144 publications
3
28
1
Order By: Relevance
“…In our HIV+ study cohort, the analysis of taxonomic composition of microbiome revealed a dominance of the Prevotella enterotype, thereby providing a rationale for study participants with looser stool 52 . Consistent with our observation, such an enrichment of Prevotella has also been independently reported by other studies in PLHIV 45–47,53–55 and MSM 44,56–58 . It is important to note within this context that SCFA are fermented among others through Prevotellaceae.…”
Section: Discussionsupporting
confidence: 90%
“…In our HIV+ study cohort, the analysis of taxonomic composition of microbiome revealed a dominance of the Prevotella enterotype, thereby providing a rationale for study participants with looser stool 52 . Consistent with our observation, such an enrichment of Prevotella has also been independently reported by other studies in PLHIV 45–47,53–55 and MSM 44,56–58 . It is important to note within this context that SCFA are fermented among others through Prevotellaceae.…”
Section: Discussionsupporting
confidence: 90%
“…Thirdly, we did not exclude the effects of HIV transmission routes on gut microbiota community composition. The use of methamphetamine and cannabis was found to affect the gut microbiota profile of HIV/AIDS patients [ 28 , 31 , 32 ]. In addition, drug use increased HIV infection and viral replication in immune cells, which accelerated the progression of AIDS [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased α-diversity is generally considered to be a marker of health and while decreased diversity has been associated with a variety of disease states [ 32 ]. Our results show that if the CD4 + T cell counts of INRs are > 200 cells/μL, they are healthier.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, changes to the gut microbiota during HIV infection are influenced by factors including ethnicity, sex, age, geography, dietary habits, lifestyle, operational factors, sample type and treatment (36)(37)(38)(39). In the present study, alterations in the intestinal mucosal microbiota and dysbiosis were identified in HIV-infected patients from Guangzhou, China.…”
Section: Discussionmentioning
confidence: 60%